Imago Dei versus Kultbild die Sapientia Salomonis als jüdisch-hellenistischer Beitrag zur antiken Bilderdebatte - Völkening, Helga (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2020)
The study spotlights the importance of ethical discourse on icons in the Book of Wisdom. Using structural, semantic, and topological analyses, it shows that parenesis about false and true images of God is an overarching theme, and contextualizes it in terms of tradition and cultural history. The text makes a unique contribution to the ancient debate on images by positing that they fulfill the imago dei invested in human beings